[2.2]Paracyclophane derivatives containing tetrathiafulvalene moieties - Sarbu, Laura G.; Bahrin, Lucian G.; Jones, Peter G.; Birsa, Lucian M.; Hopf, Henning (Beilstein Journal of Organic Chemistry, 2015)
The synthesis of [2.2]paracyclophane derivatives containing tetrathiafulvalene units has been accomplished by the coupling reaction of 4-([2.2]paracyclophan-4-yl)-1,3-dithiol-2-thione in the presence of trimethylphosphite. The 1,3-dithiol-2-thione derivative was in turn synthesized by the regioselective bromination of 4-acetyl[2.2]paracyclophane, then through the corresponding dithiocarbamates and 1,3-dithiolium salts.
Keywords: dithiocarbamates; 1,3-dithiolium salts; [2.2]paracyclophane; regioselective bromination; stereoisomers; tetrathiafulvalenes